Profil Berpikir Kritis Siswa Laki-Laki Maskulin dan Perempuan Feminin dalam Menyelesaikan Masalah Literasi Numerasi pada Asesmen Kompetensi Minimum - Reni Rachmawati; Dwi Juniati; Atik Wintarti (LP. Ma'arif Janggan Magetan, 2022)
The purpose of this research was to describe the critical thinking of masculine male and feminine female students in solving numeracy literacy problems in the minimum competency assessment. This research is a descriptive research with a qualitative approach. The data collection method used the Bem Sex Role Inventory test to determine gender tendencies, giving math ability tests, giving problem solving assignments and interviews to determine students' critical thinking profiles. The research subjects consisted of two grade VIII junior high school students with masculine male and feminine female gender with moderate math ability. The results showed that masculine male students could fulfill all critical thinking indicators, while feminine female students could not fulfill one of the critical thinking indicators, namely analyzing problems with mathematical concepts. In addition, masculine male and feminine female students have different ways or solutions in solving numeracy literacy problems in the minimum competency assessment.